Application of Lecturer Performance Index In Badan Penjaminan Mutu Lancang Kuning University - Bayu Febriadi; Pandu Putra Pratama (IJISTECH (International Journal of Information System and Technology), 2020)
In the Badan Penjaminan Mutu of Lancang Kuning University (BPM) in processing the Lecturer Performance Index (IKD) data, it still uses manual data in data processing, so this causes many problems. Among them: delays in reporting, inaccurate data, the emergence of efficiency and effectiveness of the work, overlapping data, data archiving that is not good, and other problems that result in all aspects of the existing assessment. To be able to answer all of these challenges, the author intends to submit research making Compurterization-based Quality Assurance Services application, especially in online based lecturer performance index data processing. Its usefulness is to facilitate the academic community of Lancang Kuning University in conducting data processing of Lecturer Performance Index (IKD). and it is expected that with the computerized application of Quality Assurance Services will be more effective and efficient in working. This E-IKD was created using a Mobile / Web Service application. Several actors are directly integrated with the service of this system, such as: Unit Units in the University of Lancang Kuning, Assessors, Lecturers and Administrators. Implementation methodology uses case tools which are a computer-based product, aiming to support one or more software engineering activities or processes. The purpose of the case tools is to increase the speed of analysis of university leaders, provide information related to existing business processes, improve accuracy in evaluating performance, better documentation, and use by users who are still prime. In order to provide scientific group quality assurance services or expertise and management services. The purpose of this study is the application of E-IKD (Lecturer Performance Index) based on information technology as a medium of service for lecturers and as an evaluation medium for the Badan Penjaminan Mutu (BPM) in all Units in the Lancang Kuning University environment.